'Spontaneous' volunteers unleashed: factors enabling the mobilisation of the UMT's student volunteer squad in response to disaster - Noor Idora Mohd Sukarnoor; Nurul Zahra Mohd Shamsul; Nurul Nabilah Ahmad Shahril; Vadzley Aqashah Abas; Rudiah Md Hanafiah (Penerbit Universiti Kebangsaan Malaysia, 2024)
The importance of 'spontaneous' volunteers in disaster response and recovery has been widely acknowledged for their beneficial social outcomes and significant contributions. Green Rangers (GR), a Universiti Malaysia Terengganu (UMT) organisation, emerges as a prominent example of successful nature and crisis volunteerism, potentially functioning as student-centred volunteerism as well as a partnership with other non-governmental organisations (NGOs). The need to have an efficient organisation is the main pillar for the efficacy of volunteering activities and student collaboration. Recent research indicates that students from various countries demonstrate a strong commitment to actively participate in disaster and humanitarian response endeavours. This study, however, falls short when the number of participants is limited. Besides, the perspectives and experiences of those participants may not be representative of the large community. Hence, this study aims to explore the factors that influence the 'spontaneous' volunteers' engagement while also looking for ways to enhance the organisation. Data analysis was performed using Multiple Criteria Decision Making (MCDM), which is the Analytical Hierarchy Process (AHP). The results demonstrated that the key component in encouraging volunteers is the readiness to face the disaster occurrence. Additionally, the 'Youth Engagement Effort' has been identified as a crucial factor in enhancing participation in volunteerism. Engaging youth in volunteer activities can be effectively achieved by increasing their self-awareness through disaster preparedness education and emergency management training. The respondents in the study indicated that 'Media Integration' and 'Substantial Backing' are not significant factors in the engagement of 'spontaneous' volunteers. It is anticipated that by identifying the factors that influence 'spontaneous' volunteers, we can significantly promote volunteer engagement, establish clearer roles and responsibilities, and develop more effective procedures, ultimately resulting in improved disaster response and recovery outcomes.